2015
DOI: 10.1021/acs.jpcb.5b03494
|View full text |Cite
|
Sign up to set email alerts
|

How Does Guanine–Cytosine Base Pair Affect Excess-Electron Transfer in DNA?

Abstract: Charge transfer and proton transfer in DNA have attracted wide attention due to their relevance in biological processes and so on. Especially, excess-electron transfer (EET) in DNA has strong relation to DNA repair. However, our understanding on EET in DNA still remains limited. Herein, by using a strongly electron-donating photosensitizer, trimer of 3,4-ethylenedioxythiophene (3E), and an electron acceptor, diphenylacetylene (DPA), two series of functionalized DNA oligomers were synthesized for investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 63 publications
2
34
1
Order By: Relevance
“…As mentioned previously, it is reported that the quantum efficiency of HT through three base pairs of alternating A:T is four times smaller than that of consecutive As 9. In AT3 , on the other hand, the quantum efficiency of EET is 0.20, which is smaller than T3 (0.33)6f by a factor of 1.6. Thus, EET in DNA is less affected by the alternating sequence of nucleotides than HT in DNA, probably due to efficient interactions of LUMOs in the case of EET.…”
Section: Resultsmentioning
confidence: 69%
“…As mentioned previously, it is reported that the quantum efficiency of HT through three base pairs of alternating A:T is four times smaller than that of consecutive As 9. In AT3 , on the other hand, the quantum efficiency of EET is 0.20, which is smaller than T3 (0.33)6f by a factor of 1.6. Thus, EET in DNA is less affected by the alternating sequence of nucleotides than HT in DNA, probably due to efficient interactions of LUMOs in the case of EET.…”
Section: Resultsmentioning
confidence: 69%
“…This tendency agrees with those of our previous study based on laser flash photolysis . By contrast, significant suppression of I p was observed with both CT6 and GT6, thus indicating that excess‐electron hopping between T residues was affected by the insertion of a C or G residue …”
Section: Figurementioning
confidence: 93%
“…The estimated factor is similar to our present results for interstrand and intrastrand EET from AT5 through a hopping mechanism (0.68) and almost consistent to our previous results obtained by laser flash photolysis for interstrand and intrastrand EET via an A:T sequence through a hopping mechanism (0.50) . C can thus be an electron carrier for EET through a hopping mechanism when a single G:C base pair is inserted between consecutive T residues, although multiple G:C pairs in Ts completely terminate EET in DNA through proton transfer from G to C .− in the G:C .− base pair …”
Section: Figurementioning
confidence: 99%
“…12). 65 In the transient absorption spectra of C4, the transient absorption band at 580 nm, which can be attributed to G(–H) –  : C(H)˙, the product of the proton-transfer reaction of G : C˙ – base pairs, was observed as well as 3E ˙ + . From the global analysis, the proton transfer rate was estimated to be 2.6 × 10 10 s –1 , which agreed with the theoretical estimation.…”
Section: Excess Electron Transfer In Dnamentioning
confidence: 95%